2018
DOI: 10.1111/ele.13086
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐specific relatedness, spatial clustering and reduced demographic performance in tropical rainforest trees

Abstract: Intra-specific negative density dependence promotes species coexistence by regulating population sizes. Patterns consistent with such density dependence are frequently reported in diverse tropical tree communities. Empirical evidence demonstrating whether intra-specific variation is related to these patterns, however, is lacking. The present study addresses this important knowledge gap by genotyping all individuals of a tropical tree in a long-term forest dynamics plot in tropical China. We show that related i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The higher local effect of stem abundance on species richness in tropical than in temperate forests may also be amplified by significantly higher conspecific negative density dependence in the tropics (Shao et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The higher local effect of stem abundance on species richness in tropical than in temperate forests may also be amplified by significantly higher conspecific negative density dependence in the tropics (Shao et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to influencing species diversity, soil microbes that specialize within species could also help maintain genetic diversity in plant populations by favoring the recruitment of more distantly related seedlings near established plants. A recent observational study showed that seedlings near close relatives have reduced performance (29). Other studies show that the seedlings that establish near conspecific adults are not necessarily offspring, but instead represent a diversity of genotypes (30,31).…”
Section: Fraction Of Pathogens That Are Genotype-specificmentioning
confidence: 99%
“…The uses of genotype information in plant ecology are broad including its uses in understanding the abundance, composition and diversity of herbivores and arthropod species (Crutsinger et al 2006), plant performance and coexistence (Crutsinger et al 2008;Shao et al 2018), and ecosystem services (Hersch-Green et al 2011;Zytynska et al 2011). One key aspect of genotypic data is potentially having the proportion of genetic variation which can be linked to functional trait variation and responses to the environment (Albert et al 2011).…”
Section: Genotyping and Genomicsmentioning
confidence: 99%